The Use Of Kretek Herbs For Cigarette Addicts In View Of Islamic Law - et. al., Dr. H. Najamuddin, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
‘There are differences of opinion among the ulama regarding smoking which led to the emergence of two groups in it, namely those who do not forbid it (allow smoking) and those who firmly say that smoking is haram. However, the phenomenon in the field shows that even though the prohibition of smoking has been loudly voiced, the smoking rate in Indonesia, in particular, is increasing. Therefore, herbal cigarettes are a solution for heavy smokers. Herbal cigarettes are a cylinder of paper measuring approximately 70 to 120 mm long containing tobacco ingredients and several active ingredients which are said to have beneficial pharmacological substances and effects for the body. Although in fact heavy smokers find it difficult to switch from previous cigarettes to herbal cigarettes, herbal cigarettes themselves can be said to be a solution so that smokers switch to cigarettes with lower toxic levels. Herbal cigarettes are a solution to efforts to make heavy smokers reduce their cigarette addiction or even hopefully quit eventually”.